Rites of passage: determining the efficacy of different fish passage designs along the northern Colorado Front Range - Jones, Rachel, author; Myrick, Christopher, advisor; Kanno, Yoichiro, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2022)
As historical instream barriers continue to be used and new man-made structures have the potential to further fragment river habitat, eastern Colorado fish communities face mounting challenges to survive in abbreviated river segments. Instream barriers are myriad in shape (dams, diversions, culverts, grade control, etc.) and serve a wide variety of economic and social necessities, often preventing their removal. In an attempt to restore longitudinal connectivity at instream barriers, fish passage structures of various types have recently been installed across the northern Colorado Front Range where rivers transition from high gradient mountain streams to low gradient eastern plains streams (often referred to as the transition zone). These structures are often designed with small-bodied native Plains fish species in mind. Frequently, little to no post-installation monitoring is performed for these fishways, so little is known of their comparative success. The goal of this study was to assess the passage success of the resident fish fauna at different passage structures to better understand how structure type and design affect efforts to restore connectivity. The study used long-term monitoring and short-term enclosure studies with stationary PIT tag antenna arrays that recorded movements of a free-ranging community of PIT-tagged fishes. A cast concrete rock ramp on the Cache La Poudre River and a grouted boulder wingwall bypass passage structure on the St. Vrain River were continuously monitored for nearly two years, offering insights into passage success, differences in functionality between the fishways, and the variable movement patterns of the local fish communities. Successful fishway passage was observed at both sites by numerous species over a variety of conditions, with the rock ramp passing 71% of tagged species with an overall passage rate of 55% for individuals, and the wingwall bypass passing 61% of tagged species at an overall individual passage rate of 62%. The long-term monitoring study is described in Chapter 1 of this thesis. Short-term enclosure experiments were used to evaluate both fish passage success at a given passage and to evaluate the method's capability to provide a rapid initial assessment of fishway performance. These trials added an additional pool-and-weir style passage to the two sites used in the long-term monitoring component of the study. Similar to the long-term monitoring study, the rock ramp and wingwall bypass structures both allowed passage of a majority of species, 63% and 70%, respectively, tested during the enclosure study producing overall passage rates of 49% and 64%, respectively. Conversely, fish passage at the pool-and-weir structure was largely non-existent (passage rate of 17%), suggesting it is not a satisfactory alternative for systems where the goal is to provide passage for non-jumping native fish species. The results from this study are described in detail in Chapter 2. Given the differing effects of design features and slopes on passage success for the types tested, this project suggests that future fish passage projects in these systems consider rock ramp-style structures, with specific attention to low gradients and nature-like designs where possible. In addition, long-term monitoring should be considered paramount for post-installation monitoring as it provided the greatest insight into fish passage performance. Many species, not constrained by limited time and conditions, demonstrated higher rates of passage. Greater detail of movement patterns and preferences throughout time was also obtained. However, the short-term enclosure trial process, with some refinements, can provide a valuable initial assessment of fishway functionality following construction.
Keywords: Great Plains native; rock ramp; fish passage; wing-wall bypass; PIT tag